Improving tumble turn performance in swimming—the impact of wall contact time and tuck index - David, Sina; Grove, Tamara; Duijven, Myrna v.; Koster, Paul; Beek, Peter J. (Frontiers in Sports and Active Living, 2022)
Race time can be shortened by improving turn performance in competitive swimming, but this requires insight into the optimal turn technique. The aim of the present study was to examine the effect of Wall Contact Time (WCT) and Tuck Index on tumble turn performance and their interrelations by experimentally manipulating both variables, which has not been done in previous research. Eighteen Dutch national level swimmers (FINA points 552 ± 122) performed tumble turns with three different WCTs (shorter, preferred, longer) and Tuck Indices (higher, preferred, lower), which were recorded by four underwater cameras and a wall-mounted force plate. Linear kinematic and kinetic variables, including the approach velocity (Vin), wall adaptation time (Tadapt), percentage of active WCT (aWCT), peak push-off force (FPeak) and exit velocity (Vexit), were extracted from the recordings and analyzed statistically, using the 5 m round trip time (5mRTT) as performance measure. The results indicated that the WCT should be sufficiently long to generate a high push-off force at the end of wall contact when the body is in a streamlined position. This led to a significantly shorter 5mRTT than a shorter or longer WCT. A linear mixed effect model yielded negative significant effects of WCT (-4.22, p < 0.001), FPeak (-2.18, p = 0.04), Vin (-4.83, p = 0.02), Tadapt (-2.68, p = 0.002) and Vexit (-9.52, p < 0.001) on the 5mRTT. The best overall turning performance was achieved with a Tuck Index of 0.7, which suggests that some of the participating swimmers could benefit from adapting their distance to the wall while turning, as was exemplified by calculating the optimal Tuck Index for individual swimmers. These results underscore the importance of WCT and Tuck Index vis-à-vis tumble turn performance, as well as their interrelations with other performance determining variables in this regard.